Will the Next Mark Zuckerberg Please Stay Up? - Leckart, Steven (New York Times, 2015)
The article focuses on Shariq Hashme, a 21-year-old computer science major at University of Maryland, College Park in Maryland, one of the student who join the TreeHacks, a 36-hour contest to program mobile applications, websites or hardware, which include aerial drones and virtual reality headsets. Topics discussed include immersive 3-D videoconferencing system worked by the team of Hashme, hackathons, and statement of Vikram Rajagopalan of the University of Michigan regarding hackathon.